Yin Yang 1 promotes the neuroendocrine differentiation of prostate cancer cells via the non‐canonical WNT pathway (FYN/STAT3) - Rui‐ji Liu; Zhi‐Peng Xu; Xiang Huang; Bin Xu; Ming Chen (Clinical and Translational Medicine, 2023)
Background A growing number of studies have shown that Yin Yang 1 (YY1) promotes the development of multiple tumours. The purpose of the current study was to determine the mechanism by which YY1 mediates neuroendocrine differentiation of prostate cancer (NEPC) cells undergoing cellular plasticity. Methods Using the Cancer Genome Atlas and Gene Expression Omnibus (GEO) databases, we bioinformatically analyzed YY1 expression in prostate cancer (PCa). Aberrant YY1 expression was validated in different PCa tissues and cell lines via quantitative reverse transcription polymerase chain reaction, western blotting, and immunohistochemistry. In vivo and in vitro functional assays verified the oncogenicity of YY1 in PCa. Further functional assays showed that ectopic expression of YY1 promoted cellular plasticity in PCa cells via epithelial‐mesenchymal transition induction and neuroendocrine differentiation. Results Androgen deprivation therapy induced a decrease in YY1 protein ubiquitination, enhanced its stability, and thus enhanced the transcriptional activity of FZD8. Castration enhanced FZD8 binding to Wnt9A and mediated cellular plasticity by activating the non‐canonical Wnt (FZD8/FYN/STAT3) pathway. Conclusions We identified YY1 as a novel dysregulated transcription factor that plays an important role in NEPC progression in this study. We believe that an in‐depth investigation of the mechanism underlying YY1‐mediated disease may lead to improved NEPC therapies.